Corporate Governance Recent Developments and New Trends - Boubaker, Sabri; Nguyen, Bang Dang.; Nguyen, Duc Khuong; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The current crisis has rocked the financial system worldwide and has cast doubt on the effectiveness of the existing regulatory regime. Thousands of firms have gone bankrupt and many financial institutions were bailed out by governments. The effects of the crisis have shaken emerging and developing markets alike and have not spared neither small nor large businesses. Many scholars and practitioners attribute the roots of the crisis to failures and weaknesses in the way corporate governance has been practiced since the mid-1990s. Lax board oversight of top management, short-termism and self-interested behavior have been fingered as the culprits behind recent financial turmoil. This book highlights the recent developments and new trends in corporate governance. The eighteen chapters, written by leading academics and experts, can assist corporate executives, governance bodies, investors, market regulators, and policymakers in having a global picture of major corporate governance issues.
Part I: Corporate Ownership Structure and Corporate Governance -- Part II: Issues in Executive Compensation -- Part III: Boards of Directors: Roles, duties, and Responsibilities -- Part IV: New Trends in Corporate Governance: Towards a More Effective and Sustainable Governance.
Keywords: Economics; Business planning; Economics/Management Science; Human Resource Management; Organization/Planning.; Business Strategy/Leadership.